Selection of planting date as a strategy on bean (Phaseolus vulgaris L.) yields in the Jiménez municipality, Lara state, Venezuela (Agroindustria, Sociedad y Ambiente, 2025)
The cultivation of beans plays a fundamental role in human nutrition due to its contribution of low-cost proteins to the Venezuelan diet. In order to establish the most appropriate planting time of the crop for the region, the objective was to determine the influence of the planting time on the yield in commercial bean crops in the Jiménez municipality, Lara State. The trial was carried out on the La Neblina farm located 09° 46'38.54" N and 69° 35'24.76" W, at 1710 m.a.s.l. The design used was in completely randomized blocks with 4 repetitions that allowed the 6 sowing seasons to be evaluated. Bean seeds of the Peineta variety were used. The variables evaluated were plant height, days between sowing and flowering, days between sowing and physiological maturity and yield. During the planting season of May, June and October, the Peineta cultivar showed the best development with an average height of 51.13 cm. The days to flowering and those from maturity to harvest during the different planting times were similar.  The number of fruits per plant was similar when planting was carried out in the months of May, June and July. The plants produced 19, 18 and 20 fruits.  The best yields were found in the periods of May-September and October-February with 1535 and 1800 kg.ha-1. Finally, it was evident that the best planting time for the area is from October to July
Keywords: Phaseolus vulgaris, sowing, season